Language Learning Strategies For University Unsuccessful Language Learners In Ecuador - Castro Cobo, Irene Yomar (2016)
The purpose of this study was to investigate the main learning difficulties that university unsuccessful students face in efl. A remedial intervention was designed and implemented by explicit training in appropriate learning strategies. The participants were 89 novice students from engineering and technology, 28 females and 61 males from an ecuadorian university who were enrolled in general language courses as part of their degree programs. Two treatment groups were formed of 62 students who received explicit instruction in language learning strategies during 12 weeks; the control group was formed of 27 students. The study was designed as classroom action research and the data required the employment of quantitative methods as well as qualitative. Quantitative methods selected for this study included the learning style survey (sas) as well as the strategy inventory for language learning (sill); both aspects were analyzed by relating them with